2015
DOI: 10.11114/ijsss.v3i3.770
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions about the Role of English in Students’ Assessment and Current Practices in Public Sector Higher Education Institutions in Gilgit, Pakistan

Abstract: This study is an attempt to explore different contextual issues related to the use of English language especially as second language when assessing student"s learning in different subject areas. The study focused on exploring teachers" perceptions about the role of English language in assessment and their practices related to English language proficiency of the learners, in social science subjects at Higher Education level. Based on criteria, twenty faculty members were interviewed. Document analysis was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…All the terminologies, materials and books of higher education are in English language. Din's (2015) results are also the same as the results of this study. Din's (2015) findings support the view that English language is needed for higher education because of the presence of all the terminologies and books in English.…”
Section: Emi a Global Spreading Phenomenonsupporting
confidence: 85%
See 1 more Smart Citation
“…All the terminologies, materials and books of higher education are in English language. Din's (2015) results are also the same as the results of this study. Din's (2015) findings support the view that English language is needed for higher education because of the presence of all the terminologies and books in English.…”
Section: Emi a Global Spreading Phenomenonsupporting
confidence: 85%
“…Some teachers are in favor of the use of English as a medium of instruction. Din (2015) analyzed the perceptions of teachers about English as the medium of instruction at the Higher Education Level. This study was conducted in Gilgit, Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are expected to adopt the English medium throughout their university academic life. Additionally, the students coming from public schools and colleges confront difficulty in adjusting to the university environment (Din, 2015). On the other side, research studies on feedback are important yet scant for contemporary research (Eriksson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in fifty-five countries revealed that the policy makers in the countries have considered EM instruction in universities as a mechanism of internationalizing Education and creating opportunity of the students to join the global and academic community. (Dearden, 2014) Similar studies conducted by researchers such as; Perera, Silva and Marmbe (2009), Ariyawansa (2008), Ye (2016), Din (2015), Dearden (2014) and Massler (2012) have revealed that learning the subject content in English developed the ELP skills of the students. Ball (2015) emphasizes the benefit of using Content and Language Integrated Learning (CLIL) to develop the language proficiency over teaching the language in isolation by taking the example of swimming; CLIL throws its learners into the deep end of the conceptual and procedural pool, then throws in the linguistic armbands.…”
Section: Relationship Between English Medium Education and English Language Developmentmentioning
confidence: 62%